2019
DOI: 10.3389/fimmu.2019.02722
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Immune Evasion Mechanisms of Borrelia mayonii, the Causative Agent of Lyme Disease

Abstract: Borrelia (B.) mayonii sp. nov. has recently been reported as a novel human pathogenic spirochete causing Lyme disease (LD) in North America. Previous data reveal a higher spirochaetemia in the blood compared to patients infected by LD spirochetes belonging to the B. burgdorferi sensu lato complex, suggesting that this novel genospecies must exploit strategies to overcome innate immunity, in particular complement. To elucidate the molecular mechanisms of immune evasion, we utilized various methodologies to phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 98 publications
0
24
0
Order By: Relevance
“…Various surface lipoproteins derived from the B. burgdorferi sensu lato complex, including OspC, OspE, CRASP-1, CRASP-2, and BBK32 promote pathogen survival by binding or inactivating components of the complement pathways ( Hellwage et al, 2001 ; Kraiczy et al, 2001 ; von Lackum et al, 2005 ; Garcia et al, 2016 ; Caine et al, 2017 ; Figure 4A ). Similar mechanisms, such as the inactivation of factor H (FH) and FH-like protein 1 by CRASP-1, have been recently elucidated in Borrelia mayonii , an emerging Lyme disease agent ( Walter et al, 2019 ). Although many of the complement evasion strategies identified in Borrelia are in vitro phenomena, the ability to inhibit complement may be critical for arthropod acquisition.…”
Section: Immune Evasion and Disease Severitymentioning
confidence: 84%
“…Various surface lipoproteins derived from the B. burgdorferi sensu lato complex, including OspC, OspE, CRASP-1, CRASP-2, and BBK32 promote pathogen survival by binding or inactivating components of the complement pathways ( Hellwage et al, 2001 ; Kraiczy et al, 2001 ; von Lackum et al, 2005 ; Garcia et al, 2016 ; Caine et al, 2017 ; Figure 4A ). Similar mechanisms, such as the inactivation of factor H (FH) and FH-like protein 1 by CRASP-1, have been recently elucidated in Borrelia mayonii , an emerging Lyme disease agent ( Walter et al, 2019 ). Although many of the complement evasion strategies identified in Borrelia are in vitro phenomena, the ability to inhibit complement may be critical for arthropod acquisition.…”
Section: Immune Evasion and Disease Severitymentioning
confidence: 84%
“…5 ). Following incubation with the NHS-treated reactions, the generation of the MAC was measured by applying a neoepitope-specific antibody as described previously 59 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Targeting excessive complement activation, particularly the terminal complement complex may be an effective strategy to prolong pregnancy in women with severe preeclampsia 32 . Of note, there are recent therapeutic options that block complement activation like eculizumab and ravulizumab which inhibit C5 and others blocking the cascade at different levels and thus preventing the formation of membrane attack complex 33 , 34 . Interestingly, eculizumab, which is already an approved treatment for both paroxysmal nocturnal hemoglobinuria and atypical hemolytic uremic syndrome, was utilized successfully as a temporizing treatment in a unique case of severe preeclampsia 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Of note, there are recent therapeutic options that block complement activation like eculizumab and ravulizumab which inhibit C5 and others blocking the cascade at different levels and thus preventing the formation of membrane attack complex 33 , 34 . Interestingly, eculizumab, which is already an approved treatment for both paroxysmal nocturnal hemoglobinuria and atypical hemolytic uremic syndrome, was utilized successfully as a temporizing treatment in a unique case of severe preeclampsia 34 , 35 . Our group has also demonstrated that blocking the membrane attack complex deposition on endothelial cells in vitro was achievable by adding eculizumab 31 .…”
Section: Discussionmentioning
confidence: 99%